Bird assemblages from western Sierras Grandes and Traslasierra valley in central Argentina: An important area for conservation of Chacoan and mountain birds - Vergara Tabares, David Lautaro (2018)
Between 1970 and 1980, many ornithological prospections were made in Central Argentina. With this work we intend to fill some of the existing gaps regarding such knowledge. We conducted bird surveys in the Central-western region of Córdoba province. We identified 240 bird species (63% of province`s avifauna) belonging to 48 families: 10 of which are considered under some threat category, 37 are migrants, and two are endemic to the region. Throughout a qualitative analysis of ordination, we identified three clusters of environments that share similar bird composition. Among those, the most dissimilar group was composed of aquatic environments, whereas the two other groups included wooded and anthropized environments and high altitude environments, respectively. The high bird richness recorded in a relatively small region, encompassing a variety of environments, bestows upon this area a high bird conservation value. The inclusion of this area in the system of "Important bird Areas" (IBAs) may prompt protection actions.